Lepidium meyenii (maca) attenuates titanium dioxide nanoparticle–induced hepatotoxicity in rats - Naser A. ElSawy; Nada Mohamed Mohamed Soliman; Sahar K. Ali; Ahmed Algazeery; Naief A. Dahran; Reham M. Filfilan; Hawazen A. AlGifry; Alaa M. Saleh; Noura Mostafa Mohamed; Hany A. Elkattawy (Tissue and Cell, 2027)

Pesticide residues in non-primary edible plant parts: Regulatory considerations and dietary risk assessment of guava leaves - Ganna Ashraf Ezzat; Mostafa Soliman (Regulatory Toxicology and Pharmacology, 2026)

Vitamin K2 (MK-7) as a novel cytoprotective agent in ovarian ischemia–reperfusion: Promoting functional recovery - Sahar K. Ali; Nada Mohamed Mohamed Soliman; Naser A El Sawy; Noura Mostafa Mohamed; Manal Almatrafi; Shimaa Hadhoud; Rayan G. Albarakati; Eslam Kamal Fahmy; Hany A. Elkattawy (Tissue and Cell, 2026)

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

Modulating the oxidative and inflammatory response: The therapeutic potential of vasopressin in ovarian torsion–detorsion injury - Hany A. Elkattawy; Shimaa Hadhoud; Rania Naguib; Amira Mokhtar Gobran; Eslam Kamal Fahmy; Noura Mostafa Mohamed; Naser A.El Sawy; Nada Mohamed Mohamed Soliman; Sahar K. Ali (Tissue and Cell, 2026)

Comprehensive evaluation of Balanites aegyptiaca extracts: in vitro bioactivities and in vivo antimicrobial efficacy and hematological impact on broiler chickens challenged with E. coli O78 and Clostridium perfringens type A - Asmaa Ezzat; Heba M. Salem; Sara H. Mahmoud; Ahmed Mostafa; Mohamed A. Ali; Khaled Mahmoud; Nasser S. Flefil; Tarek N. Soliman; Asmaa Negm El-Dein (Veterinary Research Communications, 2026)

Nano-liposomal berberine and vildagliptin combination: A novel therapeutic approach against oxidative stress, inflammation, autophagy dysregulation, and fibrosis in diabetic nephropathy - Areej A. Eskandrani; Safaa I. Khater; Mahran Mohamed Abd El-Emam; Rawan Altalhi; Mohamed M.M. Metwally; Tarek Khamis; Mahmoud Mostafa; Mohamed Mohamed Soliman; Shatha B. Albattal; Saed A. Althobaiti; Ola Ali; Mona I. Abdel Ati (Tissue and Cell, 2026)

Radiomodulatory and antioxidant properties of a novel pyrazine-linked quinazolinone sulfonamide derivative: Insights into renal apoptosis - Heba M. Karam; Mai H. Mekkawy; Amira Abd-ElRaouf; Aiten M. Soliman; Mostafa M. Ghorab (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Quinazolinone derivatives possess a privileged scaffold with variable pharmacological activities. This study conducted an in vitro evaluation of the pyrazine-linked quinazolinone sulfonamide derivative ( PQS ) to assess its anticancer activity, following confirmation of its safety in a normal cell line. Results revealed that PQS has a noteworthy cytotoxic effect on HepG-2 and HeLa cells, indicating its potential anticancer activity. Additionally, PQS is quite safe on normal Vero cells. Furthermore, in vivo biological activity of PQS was evaluated for its radioprotective properties in (5 Gy) irradiated mice. PQS showed mitigation of gamma radiation-induced oxidative stress, verified by the decline in MDA, ROS and NO levels, while GSH levels and GST activities were improved in kidney tissues. The apoptotic pathway was also assessed, where weak expression of caspase-3 and Bcl2-associated X protein (Bax) was noticed paired with higher expression of B-cell lymphoma 2 (Bcl2) after PQS treatment in irradiated mice. These results were confirmed by histopathological examination of kidney tissues. Besides, in-silico ADME studies revealed that compound PQS showed drug-like properties, confirmed by its physicochemical and pharmacokinetic properties. In conclusion, the results of the present study demonstrated that PQS has dual activity as a potential anticancer on HepG-2 and HeLa cancer cell lines and radio-protective activity through its anti-apoptotic and antioxidant action in the in vivo study.

Pesticide residues in imported black tea in Egypt: Occurrence, processing-induced reduction, and health risk assessment - Ahmed Elmahdy; Hend Mahmoud; Mostafa Soliman; Ahmed Bakr; Abdulrhman Gamal; Fawzy Eissa (Food Chemistry, 2026)

Nigella sativa oil (NSO): A game-changing neurorestorative strategy in cisplatin neurocognitive toxicity - Hany A. Elkattawy; Rania Hassan Mohamed Soliman; Noura Mostafa Mohamed; Shimaa Hadhoud; Amal Fahmy Dawood; Eslam Kamal Fahmy; Mohammad EL-Nablaway; Lougin M. Abdel-Ghani; Sahar K. Ali (Tissue and Cell, 2026)

Interactive effects of black sand and heat stress on coral reefs at Red Sea, Egypt - Alaa El-Din H. Sayed; Mohsen Y. Omer; Almountasirbellah Farrag; Rashad E.M. Said; Hamdy A.M. Soliman; Zeinab Bakr; Mostafa A. Khaled; Mohamed Abd El-Aal; Eman Saad; Mohamed Hamed (Marine Pollution Bulletin, 2026)

“Enhanced Biodegradation of Diquat Herbicide by Bacillus velezensis MW8SH: Insights into Performance, Degradative Pathways, and Practical Applications” - Mohamed Wageed; Hesham M. Mahdy; Mohamed H. Kalaba; Sherein I. Abd El-Moez; Mohamed A. Kelany; Mostafa Soliman (International Journal of Environmental Research, 2025)

The microbiota-gut-brain-axis theory: role of gut microbiota modulators (GMMs) in gastrointestinal, neurological, and mental health disorders - Al-Hassan Soliman Wadan; Mostafa K. Abd El-Aziz; Doha El-Sayed Ellakwa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
The modulation of gut microbiota presents promising therapeutic possibilities for various health conditions, ranging from gastrointestinal infections to neurodegenerative and mental health disorders. Among the available interventions, gut microbiota modulators (GMMs) such as probiotics and prebiotics have demonstrated significant potential in infection prevention and neuroprotection. Despite these encouraging findings, the clinical application of GMMs remains challenging due to safety concerns and inconsistent effectiveness across diverse patient populations. These factors create substantial barriers to the widespread adoption of microbiota-based therapies in clinical practice. To overcome these challenges and fully leverage the therapeutic potential of microbiota modulation, this review explores the feasibility of repurposing GMMs for managing multiple health disorders. A broad spectrum of microbiota-targeted strategies is examined, including dietary modifications, fecal microbiota transplantation, bacteriophage therapy, microbiome engineering, and immune system modulation. A particularly innovative approach involves integrating GMMs with pharmaceutical delivery systems to enhance therapeutic efficacy while mitigating potential adverse effects. This integrative strategy underscores the pivotal role of the gut microbiome in health and disease, supporting the development of precision medicine tailored to individual patient needs. By combining GMMs with targeted delivery mechanisms, this approach not only improves treatment effectiveness but also addresses critical concerns regarding safety and patient variability. Furthermore, this review outlines future research directions within the rapidly evolving field of microbiota modulation, emphasizing the necessity of comprehensive clinical trials and long-term safety evaluations. By critically assessing both the challenges and opportunities associated with microbiota-based interventions, this study provides a strategic framework for translating experimental research into viable clinical applications. A holistic approach to gut microbiota modulation has the potential to redefine treatment paradigms, offering personalized therapeutic strategies for a wide range of disorders and advancing the broader field of precision medicine.

Nutrient therapies: Boosting plant immunity for a sustainable future - Mohamed S. Attia; Amer M. Abdelaziz; Mostafa I. Abdelglil; Amr H. Hashem; Eslam K. Kandil; Eslam O. Elsawwah; Mohammed S. Helal; Salah M. Elsayed; Mustafa A. Nouh; Maryam M. Elsayed; Mohamed M. Ali; Mohamed Soliman Dora; et al. (Physiological and Molecular Plant Pathology, 2025)

Pesticide residues in Green, roasted, and capsule coffee from the Egyptian market: Occurrence, processing effects, and health risk assessment - Abdulrhman Gamal; Mohamed Abdel-Megeed; Hend Mahmoud; Mostafa Soliman; Mohamed Al-Anany; Fawzy Eissa (Food Chemistry, 2025)

Mitochondrial-based therapies for neurodegenerative diseases: a review of the current literature - Al-Hassan Soliman Wadan; Ahmed H. Shaaban; Mohamed Z. El-Sadek; Salah Abdelfatah Mostafa; Ahmed Sherief Moshref; Ahmed El-Hussein; Doha El-Sayed Ellakwa; Samah S. Mehanny (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Neurodegenerative disorders present significant challenges to modern medicine because of their complex etiology, pathogenesis, and progressive nature, which complicate practical treatment approaches. Mitochondrial dysfunction is an important contributor to the pathophysiology of various neurodegenerative illnesses, including Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). This review paper examines the current literature highlighting the multifaceted functions of mitochondria, including energy production, calcium signaling, apoptosis regulation, mitochondrial biogenesis, mitochondrial dynamics, axonal transport, endoplasmic reticulum–mitochondrial interactions, mitophagy, mitochondrial proteostasis, and their crucial involvement in neuronal health. The literature emphasizes the increasing recognition of mitochondrial dysfunction as a critical factor in the progression of neurodegenerative disorders, marking a shift from traditional symptom management to innovative mitochondrial-based therapies. By discussing mitochondrial mechanisms, including mitochondrial quality control (MQC) processes and the impact of oxidative stress, this review highlights the need for novel therapeutic strategies to restore mitochondrial function, protect neuronal connections and integrity, and slow disease progression. This comprehensive review aims to provide insights into potential interventions that could transform the treatment landscape for neurodegenerative diseases, addressing symptoms and underlying pathophysiological changes.

Corrigendum to ‘Instantaneous oxidation of levofloxacin as toxic pharmaceutical residuals in water using clay nanotubes decorated by ZnO (ZnO/KNTs) as a novel photocatalyst under visible light source’ [J. Environ. Manag. 271 (2020) 111019 / https://doi.org/10.1016/j.jenvman.2020.111019] - Mostafa R. Abukhadra; Ashraf Helmy; Mohamed F. Sharaf; Mohammed A. El-Meligy; Ahmed Tawhid Ahmed Soliman (Journal of Environmental Management, 2025)

Oxadiazole-Based Fluorescent Dyes: Photophysical Characterization and Dual Application in Latent Fingerprint Detection and Security Inks - Safa A. Badawy; Abdullah I. Kamel; Ahmed E. Soliman; Mostafa M. Abdul Wahab; Anas M. Khader; Mahmoud E. Abdelgawad; Elaria A. Ibrahim; Basant A. Mostafa; Karim M. Elmezain; Mohamed R. Elmorsy (Journal of Fluorescence, 2025)
In this study, a series of novel oxadiazole-based fluorescent dyes were synthesized and thoroughly characterized through spectroscopic analysis, theoretical modeling, and application testing. The structural design incorporated donor–acceptor motifs to promote intramolecular charge transfer (ICT), resulting in strong fluorescence across the violet-to-green spectral region (363–536 nm) with large Stokes shifts. The photophysical behavior of the dyes was investigated in solvents of varying polarity, revealing distinct solvatochromic effects and enhanced emission efficiency, particularly for diphenylamine-substituted derivatives. Density Functional Theory (DFT) calculations supported experimental observations, confirming frontier orbital distributions consistent with ICT. Thermal stability was confirmed via thermogravimetric analysis, with decomposition temperatures exceeding 250 °C. To explore practical utility, the most emissive dyes were successfully embedded into oxadiazole-based microparticles and tested for latent fingerprint development on porous and non-porous surfaces. Additionally, water-based ink formulations prepared from these dyes demonstrated excellent stability and visibility under UV light, making them suitable for covert writing and anti-counterfeiting applications. The combined structural, optical, and application-oriented results highlight the potential of these oxadiazole derivatives as multifunctional fluorescent materials for forensic and security technologies.

Overcoming challenges in the analysis of the ubiquitous emerging contaminant trifluoroacetic acid employing trap column liquid chromatography tandem mass spectrometry - Ramadan Sayed; Ahmed A. Omran; Rabie S. Farag; Hend A. Mahmoud; Mostafa Soliman (Journal of Hazardous Materials, 2025)

Allicin protects against pancreatic damage induced by zearalenone in rats by inhibiting endoplasmic reticulum stress - Amany Mohamed Shalaby; Amira Mostafa Elshamy; Abdulfatah Mohammed Albakkosh; Sulaiman Mohammed Alnasser; Mohammed Alorini; Fatima A. Jaber; Mohamed Ali Alabiad; Sabah Mohamed Hanafy; Nema Soliman; Shereen Elsayed Tawfeek (Tissue and Cell, 2025)

MircoRNAs predict and modulate responses to chemotherapy in leukemic patients - Doha El-Sayed Ellakwa; Mohamed Ahmed Abdelmalek; Mostafa M. Mostafa; Takwa E. Ellakwa; Al-Hassan Soliman Wadan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Quassia amara Linn. (Simaroubaceae): phytochemical composition and biopesticidal potential - Mohamed E. Mostafa; Ahmed Ramadan El-Rokh; Mamdouh Abdel-Mogib; M. Abd El Salam; Reda A. El-Sharkawy; Manar Refaat; Ghada N. El-Masry; Ahmed E. M. Abd El-Mageed; Amal F. Soliman (Journal of Plant Diseases and Protection, 2025)
Piercing-sucking pests infest many strategic crops worldwide, causing significant damage to crops. Botanical natural products provide several promising pesticide agents that could control these pests as an alternative to the negatively impacted synthetic insecticides. Bioassay-guided separation of the alkaloid fraction of Quassia amara Linn. woody parts against two serious pests ( Aphis craccivora Koch and Tetranychus urticae Koch) and resulted in the isolation of a new alkaloid, a β -carboline derivative 3 named quassianine, along with two known alkaloid compounds named harmine 1 and gardnerine 2 were isolated for the first time from this species using extensive chromatographic techniques. The structure elucidation of the isolated compounds was established via various 1D and 2D NMR and ESI–MS analyses. The susceptibility of both tested pests was assessed under laboratory conditions for the alkaloid and non-alkaloid fractions of Q. amara , the three pure isolated compounds and the positive control azadirachtin (Okios 3.2% EC). The alkaloid fraction was found to be the most potent fraction against A. craccivora and T. urticae with LC 50 values of 4.3 and 79.1 ppm, while harmine 1 was the most potent isolated compound with LC 50 values of 3.7 and 20.3 ppm, respectively. The most toxic alkaloid fraction and harmine compound were formulated and tested against both pests under field conditions using the LC 90 multiplicities. Furthermore, the biochemical parameters of six enzymes belonging to A. craccivora and T. urticae were estimated after the application of the LC 50 value of the alkaloid fraction and harmine 1 . Also, a detailed toxicological study on the non-target organisms, honeybees Apis cerana , coccinellid predator ladybird beetles Coccinella septempunctata and adult albino rats was conducted. Several biochemical investigations (including alanine amino transaminase, albumin, total cholesterol and reproductive hormones), as well as histopathological studies were performed. The results showed that the alkaloid fraction contains many active principles that could serve as a natural pesticide to protect some agricultural crops from many serious pests and are safer than synthetic pesticides for non-target organisms. Therefore, the Q. amara alkaloid fraction may be considered a prototype natural pesticide. Graphical abstract

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Biosynthesis of trimetallic nanoparticles and their biological applications: a recent review - Amr H. Hashem; Ebrahim Saied; Bahaa M. Badr; Mohamed Soliman Dora; Mahmoud A. Diab; Amer Morsy Abdelaziz; Fathy M. Elkady; Mohamed Abdelrahman Ali; Nasser Ibrahim Issa; Ziad A. Hamdy; Mohamed E. Nafea; Ahmed Nageh Khalifa; et al. (Archives of Microbiology, 2025)

Retraction Note: Do Zinc Supplements Enhance the Clinical Efficacy of Hydroxychloroquine?: A Randomized, Multicenter Trial - Sherief Abd-Elsalam; Shaimaa Soliman; Eslam Saber Esmail; Mai Khalaf; Ehab F. Mostafa; Mohammed A. Medhat; Ossama Ashraf Ahmed; Mohamed Samir Abd El Ghafar; Mohamed Alboraie; Sahar M. Hassany (Biological Trace Element Research, 2025)

Editorial Expression of Concern: Platelet-rich plasma as a potential therapeutic approach against lead nitrate- and/or gamma radiation-induced hepatotoxicity - Salma M. Abdel Fattah; Mostafa Saif-Elnasr; Ahmed F. Soliman (Environmental Science and Pollution Research, 2024)

Impacts of climate change and black sand on Red Sea, Egypt. A comprehensive review - Mohamed Hamed; Mostafa A. Khaled; Rashad E.M. Said; Mohamed Abd El-Aal; Sobhi M. Ghoneim; Mohsen Y. Omer; Hamdy A.M. Soliman; Eman Saad; Zeinab Bakr; Jae-Seong Lee; Alaa El-Din H. Sayed (Regional Studies in Marine Science, 2024)

BECN1 mRNA expression in breast cancer tissue; significant correlation to tumor grade - Sarah Ahmed Aglan; Ahmed Mostafa Awad; Yasmine Nagy Elwany; Sanaa Shawky; Radwa Mohamed Abdel Salam; Rasha Said Omar; Rasha Abdel Mawla Ghazala; Nada Ahmed Soliman; Marwa Ibrahim Khedr; Lamia Said Kandil; Mohamed Sultan; Yasser Hamed; et al. (Molecular Genetics and Genomics, 2024)
Breast cancer (BC) is a heterogenous disease with multiple pathways implicated in its development, progression, and drug resistance. Autophagy, a cellular process responsible for self-digestion of damaged organelles, had been recognized as eminent player in cancer progression and chemotherapeutic resistance. The haploinsufficiency of Beclin 1 (BECN1), autophagy protein, is believed to contribute to cancer pathogenesis and progression. In our study, we investigated the expression of BECN1 in a BC female Egyptian patient cohort, as well as its prognostic role through evaluating its association with disease free survival (DFS) after 2 years follow up and association of tumor clinicopathological features. Twenty frozen female BC tissue samples and 17 adjacent normal tissue were included and examined for the expression levels of BECN1. Although the tumor tissues showed lower expression 0.73 (0–8.95) than their corresponding normal tissues 1.02 (0.04–19.59), it was not statistically significant, p: 0.463. BECN1 expression was not associated with stage, nodal metastasis or tumor size, p:0.435, 0.541, 0.296, respectively. However, statistically significant negative correlation was found between grade and BECN1 mRNA expression in the studied cases, p:0.028. BECN1 expression had no statistically significant association with DFS, P = 0.944. However, we observed that triple negative (TNBC) cases had significantly lower DFS rate than luminal BC patients, p: 0.022, with mean DFS 19.0 months, while luminal BC patients had mean DFS of 23.41 months. Our study highlights the potential role of BECN1 in BC pathogenesis, showing that BECN1 expression correlates with poorer differentiation of BC, indicating its probable link with disease aggressiveness. DFS two years follow up showed that TNBC subtype remains associated with less favorable prognosis.

Clinical relevance and frequency of cytoplasmic patterns observed in ANA-Hep-2: experience of Cairo University Hospitals - Fatma Hassan Abdelraouf; Omnia DeiaaEldin Soliman; Engy Mohammad El Khateeb; Aya Erfan Mostafa (Immunologic Research, 2024)

Optimization and validation of high throughput methods for the determination of 132 organic contaminants in green and roasted coffee using GC-QqQ-MS/MS and LC-QqQ-MS/MS - Abdulrhman Gamal; Mostafa Soliman; Mohamed S. Al-Anany; Fawzy Eissa (Food Chemistry, 2024)

Green synthesis of phillipsite from natural microcline for use as an adsorbent for Cu(II), Cd(II), Pb(II), and methylene blue dye from polluted water - Fatma M. Dardir; Ezzat A. Ahmed; Mamdouh F. Soliman; Mostafa R. Abukhadra (Euro-Mediterranean Journal for Environmental Integration, 2024)

Development of LC-MS/MS analytical method for the rapid determination of Diquat in water and beverages - Mohamed Wageed; Hesham M. Mahdy; Mohamed H. Kalaba; Mohamed A. Kelany; Mostafa Soliman (Food Chemistry, 2024)

Effectiveness of cannabidiol (CBD) on histopathological changes and gene expression in hepatocellular carcinoma (HCC) model in male rats: the role of Hedgehog (Hh) signaling pathway - Samia Hussein; Nabil A. Soliman; Samih I. El Dahmy; Tarek Khamis; Reham Sameh; Fatma M. Mostafa (Histochemistry and Cell Biology, 2024)

Enhancing Soil Organic Carbon Content and Water Retention Using Polyvinyl Alcohol Cross-linked with Chitosan and Pectin - Enas Soliman; Mostafa M. Mansour (Journal of Soil Science and Plant Nutrition, 2024)
Soil organic carbon is considered a candidate without a substitute to be an important indicator of soil degradation by monitoring its amount and changes over time. Organic compounds such as chitosan (CS) and pectin (PC) can increase organic matter content in soils and provide a carbon source for microbes. Organic nanoparticles (NPs) were prepared by polymerization of CS and PC with polyvinyl alcohol (PVA), loaded with NPK nutrients, and evaluated by transmission electron microscope as well as zeta-potential (ZP). This study aims to test the effect of organic NPs on soil organic carbon (SOC) content, available water capacity (AWC), and growth of wheat plant. Thus, a pot experiment was conducted using clay soil. The treatments were NPK at two levels, viz., 50 and 85% of the recommended doses in combination with CS/PVA and PC/PVA as nano-carrier materials, as well as control treatment (85% NPK). Results showed that the loading of organic NPs with NPK nutrients obviously increases the solution stability and the positive as well as negative charges for CS/PVA (50.30 mV) and PC/PVA (− 17.80 mV), respectively. Furthermore, the using of NPK nano-fertilizers was significant for all the studied properties. Likewise, the addition of CS/PVA loaded with NPK decreased soil ZP at a range of − 13.00 to − 16.90 mV. Besides, it shows better carbon-cycling activity by increasing SOC at a range of 9.71 to 11.68 g kg −1 . The PC/PVA loaded with 50%NPK not only increases AWC with a rate of 18.23% but also sustains water-release synchronization to meet wheat plant demands.

Removal of technetium (99mTc) using modified claystone (organoclay) - Ahmed S. Ahmed; Fatma M. Dardir; Ezzat A. Ahmed; Mamdouh F. Soliman; Mostafa R. Abukhadra (Euro-Mediterranean Journal for Environmental Integration, 2024)

Correction: Irisin improves adiposity and exercise tolerance in a rat model of postmenopausal obesity through enhancing adipo-myocyte thermogenesis - Rehab E. Abo El Gheit; Reham L. Younis; Mervat H. El-Saka; Marwa N. Emam; Nema A. Soliman; Rehab M. El-Sayed; Yasser Mostafa Hafez; Norhan Ahmed AbuoHashish; Doaa A. Radwan; Howayda E. Khaled; Samar Kamel; Sawsan A. Zaitone; et al. (Journal of Physiology and Biochemistry, 2023)

Preparation and characterization of rare earth element nanoparticles for enhanced photocatalytic degradation - Rasha A. El-Kholy; Heba Isawi; Ehab Zaghlool; Elsayed A. Soliman; Mostafa M. H. Khalil; Moustafa M. Said; Abd-elhameed M. El-Aassar (Environmental Science and Pollution Research, 2023)
The present work focuses on the photocatalytic degradation of methylene blue (MB) on erbium ion (Er 3+ ) doped TiO 2 under visible light. Pure TiO 2 nanoparticles and erbium (Er 3+ ) doped TiO 2 nanocomposite (Er 3+ /TiO 2 ) NCs were synthesized using the sol–gel method. The synthesized (Er 3+ /TiO 2 ) NCs were characterized using Fourier transform infrared spectroscopy (FTIR), high resolution scanning electron microscopy (HR-SEM), elementary dispersive X-ray (EDX), X-ray diffraction (XRD), and X-ray photoelectron spectra (XPS), specific surface area (BET), zeta potential, and particle size. Different parameters were used to study their efficiency for the photoreactor (PR) and the synthesized catalyst. These parameters include pH of the feed solution, the rate of flow, the presence of an oxidizing agent (aeration pump), different ratios of nanoparticles, the amount of catalyst, and the concentrations of pollutants. An example of an organic contaminant was the dye methylene blue (MB). The result achieved using the synthesized nanoparticles (I) under ultraviolet light pure TiO 2 was found to have degraded by 85%. For (Er 3+ /TiO 2 ) NCs under visible light, dye removal increased with pH to a maximum of 77% degradation at pH 5. Furthermore, photocatalytic efficiency improves to 80% at 40 rpm (3 l/h) low motor speed. The degradation efficiency decreased to 70% when the MB concentration was increased from 5 to 30 mg/L. When oxygen content was increased using an air pump, and deterioration reached 85% under visible light, it improved performance.

The co-occurrent microplastics and nano-CuO showed antagonistic inhibitory effects on bacterial denitrification: Interaction of pollutants and regulations on functional genes - Ruirui Pang; Boqun Shao; Qiqing Chen; Huahong Shi; Bing Xie; Mostafa Soliman; Jun Tai; Yinglong Su (Science of The Total Environment, 2023)

Irisin improves adiposity and exercise tolerance in a rat model of postmenopausal obesity through enhancing adipo-myocyte thermogenesis - Rehab E. Abo El Gheit; Reham L. Younis; Mervat H. El-Saka; Marwa N. Emam; Nema A. Soliman; Rehab M. El-Sayed; Yasser Mostafa Hafez; Norhan Ahmed AbuoHashish; Doaa A. Radwan; Howayda E. khaled; Samar Kamel; Sawsan A. Zaitone; et al. (Journal of Physiology and Biochemistry, 2022)
The prevalence of obesity and its associated metabolic disorders, along with their healthcare costs, is rising exponentially. Irisin, an adipomyokine, may serve as a critical cross-organ messenger, linking skeletal muscle with adipose tissue and the liver to integrate the energy homeostasis under diet-induced obesity. We aimed to explore the putative role of irisin in the protection against obesity in a postmenopausal rat model by modulating energy expenditure (EE). Bilateral ovariectomy (OVX) was performed. After 3 weeks of recovery, the OVX rats were classified according to their dietary protocol into rats maintained on normal diets (ND) (OVX) or high-fat diet (HFD) groups. The HFD-fed animals were equally divided into OVX/HFD, or irisin-treated OVX/HFD groups. Sham rats, maintained on ND, were selected as the control group. We evaluated anthropometric, EE, and molecular biomarkers of browning and thermogenesis in inguinal white adipose tissue and skeletal muscle, and the activity of the proteins related to mitochondrial long chain fatty acid transport, oxidation, and glycolysis. HFD of OVX further deteriorated the disturbed glucose homeostasis, lipid profile, and the reduced irisin, thermogenic parameters in adipose tissue and skeletal muscle, and EE. Irisin treatment improved the lipid profile and insulin resistance. That was associated with reduced hepatic gluconeogenic enzyme activities and restored hepatic glycogen content. Irisin reduced ectopic lipid infiltration. Irisin augmented EE by activating non-shivering thermogenesis in muscle and adipose tissues and decreasing metabolic efficiency. Our experimental evidence suggests irisin’s use as a potential thermogenic agent, therapeutically targeting obesity in postmenopausal patients. Graphical abstract Irisin modulates the non-shivering thermogenesis in skeletal muscle and adipose tissue in postmenopausal model

Groundwater quality assessment using water quality index and multivariate statistical analysis case study: East Matrouh, Northwestern coast, Egypt - Rasha A. El-Kholy; Ehab Zaghlool; Heba Isawi; Elsayed A. Soliman; Mostafa M. H. Khalil; Abdel-hameed M. El-Aassar; Moustafa M. Said (Environmental Science and Pollution Research, 2022)

Dynamics of Dissolved Ions in the Rhizosphere Under Flooded Conditions - Mostafa M. Mansour; Enas Soliman (Journal of Soil Science and Plant Nutrition, 2022)
Soil salinity represents one of the major threats of land degradation and desertification under arid and semi-arid environments. It has an adverse influence on soil-water-plant relationships, posing serious challenges to agricultural productivity. The main objective of this work was to monitor the effect of farmyard manure (FYM) application and irrigation with low-quality water on the dynamics of dissolved salts and yield of rice crop ( Oryza sativa L. ) under flooded conditions. Accordingly, field and column experiments were carried out with three treatments of irrigation water, namely, tap, saline-sodic, and saline, as well as three rates of FYM application (0, 12, and 24 Mg ha -1 ). The obtained data indicated that the highest grain yields were found under the treatment with tap water followed by saline water amended with FYM at 24 Mg ha -1 . The loss of ions (Na + , HCO 3 - , Cl - , NO 3 - , SO 4 2- ) from the soil irrigated with saline water was greater than that from irrigated with saline-sodic water. The addition of FYM led to an increase in the leaching of most ions (Na + , HCO 3 - , and Cl - in particular) and decreased their accumulation in soils irrigated with saline and saline-sodic waters. The regression studies revealed that FYM application may be attributed to the increase in soil resistance against secondary salinization through improving water and salt flux out of the rhizosphere. Under flooded conditions, these findings support the hypothesis that using FYM in conjunction with saline irrigation water has a beneficial effect, while saline-sodic irrigation water should be used with a calcium source.

In vivo study of dose-dependent antioxidant efficacy of functionalized core–shell yttrium oxide nanoparticles - Samr Kassem; Mahmoud M. Arafa; Manal M. Yehya; Mostafa A. M. Soliman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Herein, we assess the dose-dependent antioxidant efficacy of ultrafine spherical functionalized core–shell yttrium oxide nanoparticles (YNPs) with a mean size of 7–8 nm and modified with poly EGMP (ethylene glycol methacrylate phosphate) and N-Fluorescein Acrylamide. The antioxidant properties of these nanoparticles were investigated in three groups of Sprague–Dawley rats (10 per group) exposed to environmental stress daily for 1 week and one control group. Groups 2 and 3 were intravenously injected twice a week with YNPs at 0.3 and 0.5 mg at 2nd and 5th day of environmental stress exposure respectively. Different samples of blood and serum were collected from all experimental groups at end of the experiment to measure oxidative biomarkers such as total antioxidant capacity (TAC), hydroxyl radical antioxidant capacity (HORAC), oxygen radical antioxidant capacity (ORAC), malondialdehyde (MDA), and oxidants concentration as hydrogen peroxide (H 2 O 2 ). The liver, brain, and spleen tissues were collected for fluorescence imaging and histopathological examination in addition to brain tissue examination by transmission electron microscope (TEM). Inductively coupled plasma-mass spectrometry (ICP-MS) was used to estimate YNPs translocation and concentration in tissues which is consecutively dependent on the dose of administration. Depending on all results, poly EGMP YNPs (poly EGMP yttrium oxide nanoparticles) can act as a potent direct antioxidant in a dose-dependent manner with good permeability through blood–brain barrier (BBB). Also, the neuroprotective effect of YNPs opening the door to a new therapeutic approach for modulating oxidative stress–related neural disorders. Highlights • The dose-dependent antioxidant efficacy of ultrafine spherical functionalized core–shell yttrium oxide nanoparticles (YNPs) with a mean size of 7–8 nm and modified with poly EGMP (ethylene glycol methacrylate phosphate) and N-Fluorescein Acrylamide was assessed. • The dose of administration directly affecting the brain, liver, and spleen tissues distribution, retention, and uptake of YNPs and direct correlation between the absorbed amount and higher dose administered. • YNPs can act as a potent direct antioxidant in a dose-dependent manner with good permeability through blood–brain barrier (BBB). Graphical abstract

RETRACTED ARTICLE: Do Zinc Supplements Enhance the Clinical Efficacy of Hydroxychloroquine?: a Randomized, Multicenter Trial - Sherief Abd-Elsalam; Shaimaa Soliman; Eslam Saber Esmail; Mai Khalaf; Ehab F. Mostafa; Mohammed A. Medhat; Ossama Ashraf Ahmed; Mohamed Samir Abd El Ghafar; Mohamed Alboraie; Sahar M. Hassany (Biological Trace Element Research, 2021)

Functionalized Core-Shell Yttrium Oxide Nanoparticles as Antioxidants Agents in Heat Stressed Rats - Samr Kassem; Medhat Mohamed; Hossam Sayour; Francesco Canfarotta; Sergey Piletsky; Mostafa A.M. Soliman (Biological Trace Element Research, 2020)

Efficiency of Candida tropicalis for Potential Degradation of Metalaxyl in the Aqueous Media - Aly Soliman Hamed Derbalah; Antar El-Banna; Mostafa Saad Allah (Current Microbiology, 2020)

Cross talk between Hsp72, HMGB1 and RAGE/ERK1/2 signaling in the pathogenesis of bronchial asthma in obese patients - Nema Ali Soliman; Muhammad Tarek Abdel Ghafar; Reham Mohamed El Kolaley; Yasser Mostafa Hafez; Rehab E. Abo Elgheit; Marwa Mohamed Atef (Molecular Biology Reports, 2020)

Efficient removal of Sr ions from water utilizing a novel Ni-/Fe-doped spongy apatite through fixed bed column system: optimization and realistic application - Mostafa R. Abukhadra; Fatma M. Dardir; Ezzat A. Ahmed; Mamdouh F. Soliman (Clean Technologies and Environmental Policy, 2019)

Correction to: Platelet-rich plasma as a potential therapeutic approach against lead nitrate- and/or gamma radiation-induced hepatotoxicity - Salma M. Abdel Fattah; Mostafa Saif-Elnasr; Ahmed F. Soliman (Environmental Science and Pollution Research, 2018)

Platelet-rich plasma as a potential therapeutic approach against lead nitrate- and/or gamma radiation-induced hepatotoxicity - Salma M. Abdel Fattah; Mostafa Saif-Elnasr; Ahmed F. Soliman (Environmental Science and Pollution Research, 2018)

Spongy Ni/Fe carbonate-fluorapatite catalyst for efficient conversion of cooking oil waste into biodiesel - Mostafa R. Abukhadra; Fatma M. Dardir; Mohamed Shaban; Ezzat A. Ahmed; Mamdouh F. Soliman (Environmental Chemistry Letters, 2018)

The use of multiplex PCR for the diagnosis of viral severe acute respiratory infection in children: a high rate of co-detection during the winter season - A. A. El Kholy; N. A. Mostafa; A. A. Ali; M. M. S. Soliman; S. A. El-Sherbini; R. I. Ismail; N. El Basha; R. I. Magdy; N. El Rifai; D. H. Hamed (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The genus Apterogyna in Saudi Arabia, with description of a new species and a new record (Hymenoptera: Bradynobaenidae: Apterogyninae) - Ahmed Mostafa Soliman; Neveen Samy Gadallah; Hathal Mohammed Al Dhafer (Biologia, 2015)

Hydrological analysis and flood mitigation at Wadi Hadramawt, Yemen - Mostafa M. Soliman; Abdel Hamid M. H. El Tahan; Ayman H. Taher; Wael M. H. Khadr (Arabian Journal of Geosciences, 2015)

Heterologous expression of thermostable esterase gene from Geobacillus thermoleovorans YN under different expression promoters - N. A. Soliman; Y. R. Abdel-Fattah; H. E. Mostafa; A. Gaballa (International Journal of Environmental Science and Technology, 2014)

Synthesis of some new thiazolopyrane and thiazolopyranopyrimidine derivatives bearing a sulfonamide moiety for evaluation as anticancer and radiosensitizing agents - Dalal A. Abou El Ella; Mostafa M. Ghorab; Helmy I. Heiba; Aiten M. Soliman (Medicinal Chemistry Research, 2012)